2015
DOI: 10.1590/s1806-37132015000000057
|View full text |Cite
|
Sign up to set email alerts
|

Functional improvement in patients with idiopathic pulmonary fibrosis undergoing single lung transplantation

Abstract: Objective: To evaluate the changes in lung function in the first year after single lung transplantation in patients with idiopathic pulmonary fibrosis (IPF). Methods: We retrospectively evaluated patients with IPF who underwent single lung transplantation between January of 2006 and December of 2012, reviewing the changes in the lung function occurring during the first year after the procedure. Results: Of the 218 patients undergoing lung transplantation during the study period, 79 (36.2%) had IPF. Of those 79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
(32 reference statements)
3
8
0
1
Order By: Relevance
“…In addition, they demonstrated that elevated pre‐LTx mean pulmonary artery pressure returned to normal value post‐LTx . We observed similar findings in our study, with PFT values 1 month after LTx surgery of FVC 2.22 ± 1.16 L (52.38% ± 27.72%), FEV 1 1.85 ± 0.97 L (54.56% ± 29.4%), TLC 3.43 ± 1.74 L, and RV 1.23 ± 0.6 L, and continuous improvement throughout the first year of follow‐up: FVC 3.08 ± 1.58 L (65.88% ± 34.47%), FEV 1 2.14 ± 1.13 L (71.20% ± 37.64%), which is similar to findings among IPF patients after LTx …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, they demonstrated that elevated pre‐LTx mean pulmonary artery pressure returned to normal value post‐LTx . We observed similar findings in our study, with PFT values 1 month after LTx surgery of FVC 2.22 ± 1.16 L (52.38% ± 27.72%), FEV 1 1.85 ± 0.97 L (54.56% ± 29.4%), TLC 3.43 ± 1.74 L, and RV 1.23 ± 0.6 L, and continuous improvement throughout the first year of follow‐up: FVC 3.08 ± 1.58 L (65.88% ± 34.47%), FEV 1 2.14 ± 1.13 L (71.20% ± 37.64%), which is similar to findings among IPF patients after LTx …”
Section: Discussionsupporting
confidence: 89%
“…Survival for patients with silicosis at 6 months, and at 1 and 3 years post‐LTx were 86%, 86%, and 76%, respectively . In contrast, the survival rates we observed in our LTx group at 1, 3, and 5 years post‐LTx were 69%, 44%, and 25%, respectively, similar to a recent report on IPF patients undergoing single LTx at ISCMPA (first‐year survival, 70%) …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Out of the seven studies that present survival rates of BLTx The other studies align with the findings of the UNOS Registry and ISHLT registry, which outline that BLTx has improved survival for IPF patients over SLTx (14)(15)(16)(17)(18)(19)(20)(21)(22). In their cohort of 469 patients, 82 of which had IPF, Mason et al found that patients receiving BLTx had better riskunadjusted survival than those receiving SLTx, with 1-year survival at 81% and 67%, and 5-year survival at 55% and 34%, respectively.…”
Section: Sltx Vs Bltx: Head-to-head Studiessupporting
confidence: 52%